Ethnographie d’une création en action - Francesca Cozzolino (Images Re-Vues)
This article is based on the ethnography of Pierre di Sciullo's exhibition entitled "Typoéticatrac. Les mots pour le faire "(trans. “Typoéticatrac. Words to do things”) which took place between April and July 2017 at the art center Le Bel Ordinaire (Pau). The description we interwoven enables one to see the creative uses of technology, and the way in which  the exhibited objects take on part of their meaning in the course of their making process. These are singular objects, whose trajectories we have traced, from the collection of the materials, that let them come into being (objects recovered in a thrift center), to their manufacture by assembly, and finally their symbolic requalification as "sound machines". Activated by simple mechanical operations (friction, friction, percussion, runoff, vibration), these machines offered the public the opportunity to play with new sounds that intended to evoke the sound of consonants. The creation process enlightens a heuristic of art made as much from practical thoughtful approach as from experiments, trial and error.